Literature Study on the Utilization of Audiovisual Media in Hànzì Learning in the Digital Era - Nurul Khasanah; Nur Muji Arti Hidayah; Jennica Debby Verima Latuharhary (Universitas Negeri Surabaya, 2025)
All students will go through hànzì study as part of their Chinese language proficiency journey. Hànzì learning is frequently seen by students as a challenging aspect of learning Chinese, particularly when it comes to writing and character recognition. As the digital age progresses, Hànzì learning is being improved through the use of audiovisual materials including cartoon movies, animated videos, and online resources like YouTube. This study aims to provide a thorough analysis of the literature on the use of audiovisual materials for Hànzì learning at different educational levels. Researching the literature by examining pertinent papers, journals, and reports was the approach taken. The findings of this study demonstrate that audiovisual materials are a successful teaching tool for Mandarin throughout a range of educational levels, from early childhood education to vocational schools. For elementary school students, animated movies and music videos enhance vocabulary acquisition; they receive an average score of 90–100 and complete them all. 90% of Vocational High School students acknowledge the value of YouTube videos like Little Fox Chinese, which aid in pronunciation and contextual comprehension. Over 80% of youngsters in early childhood education centers surpassed the competency level by watching educational films.